The effect of coated nano-hydroxyapatite concentration on scaffolds for osteogenesis. (January 2020) - Jang, Hyun Jun; Lee, Eun Cheol; Kwon, Gu Joong; Seo, Young Kwon
In this study, we fabricated a silk scaffold containing nano-hydroxyapatite (nano-HAp) for bone tissue engineering applications. The sericin-extracted silk scaffolds were coated with 0.30, 0.15, and 0.03 g of nano-HAp. The scaffolds were soaked in a 1% type I atelocollagen solution and lyophilized. Scaffolds were crosslinked with 0.02% carbodiimide and lyophilized for 48 h, followed by sterilization with γ-irradiation at 10 kGy. The scaffold properties were investigated by energy-dispersive X-ray spectroscopy and atomic force microscope. A typical spectrum of the inorganic crust and the electron diffraction patterns revealed peaks for calcium, phosphorus, and oxygen atoms. Root mean square values of the control and experimental group surfaces were 5.60 and 40.32 nm. The width of nano-HAp was in the approximate range 100–150 nm, and the height was approximately 350 nm. Dental pulp cells were seeded at a density of 2.8 × 10 4 cells/cm 2 and cultured for 3 weeks in a growth medium. The cells were then cultured for 4 weeks in differentiation medium and were transplanted into a nude mouse. The biopsy was processed at 8 weeks. The use of 0.15 g of nano-HAp led to the greatest collagen type III, fibronectin, osteocalcin, osteopontin, osteonectin, osteoprotegerin, and BMP-2 mRNA levels in vitro after 4 weeks in differentiation medium. Western blotting analysis to elucidate signaling pathways was performed. β-Catenin, phosphorylated-ERK, p38 phosphorylation most increased when 0.15 g of nano-HAp was used compared with the control group. In the histological comparison, osteocalcin and osteopontin synthesis were higher for the silk scaffold that contained 0.15 g of nano-HAp. Among the scaffolds, samples containing 0.15 g of nano-HAp were the most effective for osteogenesis. Therefore, this will be a suitable substrate as a biomaterial for bone tissue engineering applications.